2010
DOI: 10.3233/jad-2010-1222
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in the Progression of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is characterized pathologically by the presence of senile plaques, neurofibrillary tangles, and synapse loss. Increasing evidence supports a role of amyloid beta-peptide (Abeta)-induced oxidative stress in the progression and pathogenesis of AD. In this review, we summarize evidence for a role of oxidative stress in the progression of AD by comparing the appearance of the same oxidized brain proteins from subjects with mild cognitive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(211 citation statements)
references
References 129 publications
(204 reference statements)
5
204
0
2
Order By: Relevance
“…AD is the most prevalent form of human dementia, with a frequency that progressively increases in aging societies (10). A pivotal role in development and progression of late-onset AD, and other age-dependent dementias, has been attributed to inflammatory and oxidative stress cascades in the brain (11,12), which are potentiated by elevated levels of nitrosating and oxidizing species (13,14).…”
mentioning
confidence: 99%
“…AD is the most prevalent form of human dementia, with a frequency that progressively increases in aging societies (10). A pivotal role in development and progression of late-onset AD, and other age-dependent dementias, has been attributed to inflammatory and oxidative stress cascades in the brain (11,12), which are potentiated by elevated levels of nitrosating and oxidizing species (13,14).…”
mentioning
confidence: 99%
“…There is consistent evidence in literature showing the involvement of free radical-induced oxidative damage in the etiopathogenesis of AD, since oxidative stress is one of the earliest events in AD pathogenesis [18,[80][81][82]. Moreover, oxidative damage has been shown in the blood, CSF and brain of neurological patients with probable AD [83][84][85].…”
Section: Involvement Of Sam In Oxidative Stress and Neurodegenerationmentioning
confidence: 51%
“…Normal functioning of this metabolic cycle is essential for growth and development and impairment of this metabolism; transmethylation efficiency is associated with many diseases like cardiovascular diseases [4][5], liver diseases [6][7][8][9], neural tube defects [10] and brain diseases [11][12][13][14][15][16]. One-carbon metabolism alterations, low methylation and oxidative stress are all linked to Late Onset Alzheimer's Disease (LOAD) [17][18][19][20][21][22][23][24] Moreover, wide confirmed reports underline the role of SAM dependent reactions in age related neurodegeneration also showing the role of SAM supplementation in restoring one-carbon metabolism alterations, particularly in neurodegenerative diseases [25][26][27][28][29]. SAM is currently marketed as a nutritional supplement worldwide, whereas it is sold as a prescription drug in several countries of the European Union.…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence supported that free radical induced oxidative damage may play a role in the pathogenesis of AD (30,31). Features of brain, including a high content of readily oxidized fatty acids, high use of oxygen, and low levels of antioxidants, make it especially sensitive to oxidative damage.…”
Section: Free Radical Oxidative Damagementioning
confidence: 99%
“…Studies found that puerarin had potent effects in improving learning and memory disorders induced by scopolamine or D-galactose in a mouse model (65). Yan et al reported that puerarin protected neurons against apoptosis in the cortex and hippocampus of AD rats caused by Aβ [25][26][27][28][29][30][31][32][33][34][35] through downregulating Aβ and Bax expression in brain tissues, therefore alleviating the spatial learning and memory impairment of diseased animals (66). The anti-AD effects of puerarin were also suggested to be related to its abilities in decreasing the lipid peroxidase levels and increasing superoxide dismutase levels in brain tissues, enhancing cerebral blood flow, and improving brain microcirculation (67,68).…”
Section: Puerarinmentioning
confidence: 99%